Recent progress of metal organic frameworks-derived composites in adsorptive removal of pharmaceuticals. (1st November 2022) - Mahmoud, Mohamed E.; Elsayed, Sarah M.; Mahmoud, Safe ELdeen M.E.; Nabil, Gehan M.; Salam, Mohamed Abdel
Graphical abstract: In this review article, the historical, structural and stability features of MOFs are described. Removal of most commonly used pharmaceuticals from water by the action of MOFS are also surveyed and covered. In addition, the future developments of MOFs in pharmaceuticals removal are pointed out. Abstract: In the last two years, excessive amounts of antibiotics and other drugs were used to minimize the symptoms of COVID-19 as well as other newly discovered modified viruses. This has daily resulted in generation and release of substantial amounts of these drugs and their metabolites to water systems as hazardous pollutants. Upon entrance of such pharmaceutical residues into water, they incorporate, interfere and uptake by a number of activities. That is why; pharmaceutical residues or pollutants in wastewater must be effectively removed before being evacuated to environments. Water treatment via adsorption technique is highly recommended due to the wide varieties of adsorbents, biosorbents and nanosorbents with their various advantages as cost effective, high surface area, excellent binding ability and superior capacity for all pollutants. Metal-organic frameworks (MOFs) and MOFs-derived composites are representing an important class of adsorbents as porous or spongy materials and thus, recently attracted research interests and industrial applications in different disciplines. The reasons for such high global performance of developed MOFs-derived composites are mainly devoted to their incorporated characteristics as high surface area, tunable micro-porosity, spongy like structures and low density-formed skeleton. Therefore, MOFs-derived composites are regarded as perfect functional porous materials for removal of various pollutants as pharmaceuticals and drugs. For this reason, the present review is devoted to cover the recent applications of modified and functionalized MOFs-derived composites for adsorbing various types of pharmaceuticals from water and wastewater. The future developments of MOFs-derived composites are also pointed out to summarize the major gaps as guidelines for progress of MOFs-derived materials in the coming few decades.